A-255 Beyond The Gut: Implications of Socially-Inclusive Food Policies for the Brain. (17th August 2022) - VanLandingham, Hannah; Ellison, Rachael L; Cladek, Andrea; Hussaini, Halima; Khan, Humza; Gonzalez, Christopher; Bozeman, Joe; Theis o, Thomas
Abstract: Objective: Socially-inclusive food policies impact more than physical health, namely, psychological and cognitive well-being. We will provide a comprehensive review and visual relationship of mechanisms by which sociocultural factors (via socially-inclusive food policies), impact lifelong mental/cognitive health. The relationship between diet and cognitive/mental health has implications for systematically disadvantaged communities. Methods: Inclusion criteria: empirical studies published between 1995-2021 in English peer reviewed journals that included/addressed the impact of nutrition on mental health and/or cognition, searched for through electronic databases (e.g., Google Scholar). Keywords: terms related to nutrition (e.g., food policy, microbiome), cognition (e.g., neuropsychology, memory), development (e.g., perinatal, prenatal, older adulthood), mental health (e.g., stress, psychological outcomes). Results: Access to food, or the lack thereof, can play a significant role in mental health and cognitive outcomes. However, the relationship between food policies and mental health is at least as complex as the relationship between food insecurity and mental stress. Specifically, the microbiota-gut-brain axis (MGB axis) shows increasing evidence linking the human microbiome to clinical psychopathology. Conclusion: What we eat, and thereby food policies that impact what we eat and what access we have to food, significantly impact cognition and mental health via multiple mechanisms. Responses related to the MGB axis (e.g., inflammation, cerebro/cardiovascular diseases) are associated with poorer outcomes, especially in marginalized communities with limited access to healthy food and higher rates of risk factors due to systemic discrimination and inequities. Nutritional interventions and addressing nutritional deficits serve as one modifiable way to potentially prevent and reduce the severity of cognitive and mental health symptoms.